Effect of investigational kisspeptin/metastin analog, TAK-683, on luteinizing hormone secretion at different stages of the luteal phase in goats - RAHAYU, Larasati Puji (J Reprod Dev, 2017)
This study aimed to examine the response of luteinizing hormone (LH) secretion and ovarian steroid profile to TAK-683, an investigational metastin/kisspeptin analog, through treatment during different stages of the luteal phase in goats. Nine cycling Shiba goats (4.4 ± 2.3 years old) were assigned to early luteal phase (ELP, n = 4), mid-luteal phase (MLP, n = 4), and control (n = 5) groups. The ELP and MLP groups were administered 50 µg of TAK-683 intravenously on either day 5 or between days 7–14 after ovulation, respectively. The control group received vehicle between days 7–14 after ovulation. Blood samples were collected at 10-min (2–6 h), 2-h (6–24 h), and 24-h (24–96 h) intervals after treatment. Significant increases in plasma LH concentration were detected during the periods of 3 to 5 h and 2 to 5 h in the ELP and MLP groups, respectively. Estradiol concentrations continuously increased with the rise of basal LH secretion after TAK-683 treatment in two goats of the ELP group with a surge-like release of LH, but not in the goats without LH surge, i.e. the MLP and control group ones. Plasma progesterone concentration and the lengths of estrous cycle in all groups did not change significantly from the time before and after treatment. Present findings indicate that the responses of LH and ovarian steroids to treatment with TAK-683 depend on the stage of the luteal phase of the estrous cycle. We suggest that the stimulatory effects of TAK-683 on LH secretion are reduced in the process leading to the mid-luteal phase in cycling goats.